The Influence of Accounting Student Perceptions About Taxes, Tax Brevet and Motivation on Career Interest in Taxation - Wahyu Al Akbar; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to examine and obtain evidence regarding (1) accounting students' perceptions of taxation on interest in a career in taxation, (2) tax brevet on interest in a career in taxation, (3) motivation for interest in a career in taxation. This research is a type of quantitative research with hypothesis testing. The sample used in this study was 85 accounting students at Muhammadiyah Sidoarjo University consisting of semesters 6, 8 and 10. The analytical tools used were multiple linear regression test, correlation coefficient (R), coefficient of determination (R²), t test, and test. F using the SPSS version 18.0 for windows program. This primary data was obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of the validity and reliability test showed that the data were valid and reliable. The results of the t-test indicate that the student's perception of taxes, tax brevet, and motivation partially affect the interest in a career in taxation.